Pengaruh Kesenangan Berbelanja, Persepsi Harga dan Impulsive Buying Terhadap Keputusan Pembelian di E-commerce Shopee Live (Studi Pada Pelanggan Shopee Live di Kec. Lowokwaru Kota Malang) - Balgista, Tiara Wildana; Wahono, Budi; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the influence of shopping pleasure, price perception, and impulsive buying on purchasing decisions on Shopee Live e-commerce. Using the multiple linear regression method, this research focuses on explanatory research with a quantitative approach. A sample of 75 customers was determined using the Malhotra formula. Data analysis was carried out using SPSS, including validity test, reliability test, normality test, classical assumption test, hypothesis test and coefficient of determination test (R2). The research results show that overall shopping pleasure and price perception have a significant effect on purchase satisfaction in e-commerce shoppe live. Meanwhile, impulsive buying does not have a significant influence on shopee live customers' purchasing decisions. Keywords: Shopping Pleasure, Price Perception, Impulsive Buying, Purchase Decision